Knowledge networks and the role of family firms: The case of an Italian regional cluster - Stefano Ghinoi; Riccardo de Vita; Bodo Steiner; Alessandro Sinatra (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Studies on open innovation (OI) have highlighted the importance of inter-organizational knowledge networks. However, little is known about OI networks established by family firms, and their roles in such knowledge networks. By focusing on one of the most important Italian footwear clusters, this paper applies Social Network Analysis to investigate the role of family firms in exchanging knowledge according to their intra-cluster position and extra-cluster openness. Our results provide novel evidence on the role of family firms in OI networks, as they suggest that family firms mainly operate as gatekeepers in the technological and managerial networks, while they act as external stars in the market and managerial networks.
Keywords: 650; knowledge network; open innovation; regional cluster; social network analysis